Nitrogen use efficiency—a key to enhance crop productivity under a changing climate - Govindasamy, Prabhu; Muthusamy, Senthilkumar K.; Bagavathiannan, Muthukumar; Mowrer, Jake; Jagannadham, Prasanth Tej Kumar; Maity, Aniruddha; Halli, Hanamant M.; G. K., Sujayananad; Vadivel, Rajagopal; T. K., Das; Raj, Rishi; Pooniya, Vijay; et al. (Frontiers in Plant Science, 2023)
Nitrogen (N) is the most important growth and yield limiting factor in crop production. On a global scale, N is the most widely used fertilizer nutrient in agriculture. Studies have shown that only 40–50% of the applied N has been used effectively, while the rest is lost in different forms in the environment. It affects the environmental quality and life on the earth. Consequently, enhancing Nitrogen Use Efficiency (NUE) is an area that receives considerable attention in various crop improvement programs and agronomic management systems. Volatilization, surface runoff, leaching, and denitrification of N are the major processes responsible for low N use. Improving NUE through agronomic management practices and high-throughput technologies would reduce the need for intensive N application and minimize the negative impact of N on the environment. The harmonization of agronomic, genetic, and biotechnological tools can improve the efficiency of N assimilation in crops as well as align agricultural systems with global needs to protect environmental functions and resources.